Information technology & media sociology in a (still) pandemic world. Issue 5 (4th April 2022) - Davis, Jenny L.; Kidd, Dustin; Li, Muyang; Aalders, Rachel; Burgese, Tyler
ABSTRACT: The current period of disruptive social change is inextricably bound up with new means and modes of communication, information, and media streams. The Communication, Information Technologies & Media Sociology section of the American Sociological Association (CITAMS) locates these factors at the center of our collective interests, investigating them through a plethora of methods, theories, and empirical cases. Each year, CITAMS runs a special issue in ICS showcasing select works presented at the previous year's American Sociological Association conference and the affiliated Media Sociology preconference. Papers in the 2022 CITAMS Special Issue reflect a social context defined by a prolonged global pandemic and wrought by democratic uncertainty. Across these social circumstances, technology and media loom large. Simultaneously, everyday life continues and classic CITAMS scholarship sustains relevance for the ways people interact, construct identity, consume, and mobilize. All of this and more are contained in the pages of this year's Special Issue, from which readers can get a sense of what CITAMS has to offer and consider how their own work may fit within the broad CITAMS umbrella.